Child-Centered Communication. The Narrative of USHMM’s Daniel’s Story - Zaborski, Marcin (Roczniki Nauk Społecznych, 2025)
This case study analyses the exposure strategy employed by the creators of the exhibit “Remember the Children: Daniel’s Story” presented at the United States Holocaust Memorial Museum. It tells the story of a fictional Jewish family living during the Nazi era and discusses key facts about the Holocaust, and is aimed at children. What kind of message was prepared for them? What tools do the exhibit’s creators use to present the story of the traumatic past? Do they take into account the predisposition and emotional capacity of the young audience? The author of the article seeks answers to these questions by examining the compositional structure of the exhibit and its various elements.